The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.jclinepi.2021.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Reporting and methodological quality of COVID-19 systematic reviews needs to be improved: an evidence mapping

Abstract: Objectives To assess the reporting and methodological quality of COVID-19 systematic reviews, and to analyze trends and gaps in the quality, clinical topics, author countries, and populations of the reviews using an evidence mapping approach. Study Design and Setting A structured search for systematic reviews concerning COVID-19 was performed using PubMed, Embase, Cochrane Library, Campbell Library, Web of Science, CBM, WanFang Data, CNKI, and CQVIP from inception until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 28 publications
4
54
0
Order By: Relevance
“…Out of 17 available reviews published before September 1, 2020, 5 (29%) were found to be of low and the remaining 12 (71%) of critically low quality. This is also in line with Li et al [31] who assessed 63 systematic reviews (25%) to have low and 150 (62%) to have critically low quality. The authors also evaluated reporting using PRISMA [77], and the median score was 14 (10-18).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Out of 17 available reviews published before September 1, 2020, 5 (29%) were found to be of low and the remaining 12 (71%) of critically low quality. This is also in line with Li et al [31] who assessed 63 systematic reviews (25%) to have low and 150 (62%) to have critically low quality. The authors also evaluated reporting using PRISMA [77], and the median score was 14 (10-18).…”
Section: Discussionsupporting
confidence: 89%
“…In some recent studies and clinical trials, AI has been demonstrated to match or even exceed the performance of expert radiologists, which could potentially offer expedited and less expensive diagnostics [2530]. A recent study and meta-analysis by Li et al [31] with 31,587 identified and 82 included studies shows deep learning is capable of slightly outperforming health care professionals in detecting diseases from medical images with a pooled sensitivity of 87% (vs 86% of health care professionals) and pooled specificity of 93% (vs 91% respectively). Overlapping confidence intervals suggest that there is no statistically significant difference in performance between AI and human.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the published work was not assessed in our analysis, given the broad scope and huge diversity of the included papers. Nevertheless, many surveys of the quality of COVID-19 publications already exist [15,[25][26][27][28][29][30][31][32][33][34][35][36][37]. Although existing surveys of the quality of COVID-19 research do not cover all subfields of investigation and quality is often difficult to measure precisely, the consistent finding of the high prevalence of low-quality studies across very different types of study designs suggests that a large portion ( perhaps even the large majority) of the immense and rapidly growing COVID-19 literature may be of low quality.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, many surveys of the quality of COVID-19 publications already exist. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] Although existing surveys of the quality of COVID-19 research do not cover all subfields of investigation and quality is often difficult to measure precisely, the consistent finding of high prevalence of low quality studies across very different types of study designs suggests that a large portion (perhaps even the large majority) of the immense and rapidly growing COVID-19 literature may be of low quality. Moreover, massive productivity has been described in the pre-COVID era, as affecting researchers across many fields 39 and may be a particular feature for COVID-19 research.…”
Section: Discussionmentioning
confidence: 99%